HUBUNGAN TINGKAT PENGETAHUAN DAN PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI (MASKER) DENGAN GANGGUAN PERNAPASAN - Novita Sekarwati; Subagiyono Subagiyono (STIKES Wira Husada Yogyakarta, 2018)
Background: The advances in the ﬁ eld of industry in Indonesia give various positive effects that are the work opportunities, the improvement of transportations and communications and the increasing of socio-economic level of the community. Industrial activity in general is also a sector that is potential as a source of pollution that would be detrimental for the health and the environment. Objective: To ﬁ nd out the relationship between knowledge and behavior of the use of personal protective equipment (masks) with respiratory disorder in the employees of furniture industry in District of Sewon Bantul Yogyakarta Method: This research method is quantitative research with cross sectional design. Result: There is no relationship between the level of knowledge with respiratory disorder in the employees of furniture industry in District of Sewon Bantul Yogyakarta with p-value 0,878> 0,05. There is a relationship between the behavior of the use of personal protective equipment (masks) with respiratory disorder in the employees of furniture industry in District of Sewon Bantul Yogyakarta with a value 0,001 of p-value<0,05.Conclusion: There is no relationship between the levels of knowledge with respiratory disorder in the employees of furniture industry in the District of Sewon Bantul Yogyakarta. There is a relationship between the behaviors of the use of personal protective equipment (masks) with respiratory disorder in the employees of furniture industry in District of Sewon Bantul Yogyakarta.